Stereotypen geht es gut. Ein Beitrag zu stereotypischem Denken polnischer und deutscher Studierender am Beispiel eines E-Mail-Tandemprojekts - PAWŁOWSKA-BALCERSKA, AGNIESZKA (Glottodidactica, 2019)
The article attempts to approach stereotypes from both the theoretical and empirical perspectives. First, it endeavours to explain the term “stereotype”, looks into its characteristics and functions and then presents selected aspects of the Polish-German tandem project devoted to stereotypical thinking.